Feasibility of cardiac MR thermometry at 0.55 T - Mooiweer, Ronald; Rogers, Charlotte; Vidya Shankar, Rohini; Razavi, Reza; Neji, Radhouene; Roujol, Sébastien (Frontiers in Cardiovascular Medicine, 2023)
Radiofrequency catheter ablation is an established treatment strategy for ventricular tachycardia, but remains associated with a low success rate. MR guidance of ventricular tachycardia shows promises to improve the success rate of these procedures, especially due to its potential to provide real-time information on lesion formation using cardiac MR thermometry. Modern low field MRI scanners (<1T) are of major interest for MR-guided ablations as the potential benefits include lower costs, increased patient access and device compatibility through reduced device-induced imaging artefacts and safety constraints. However, the feasibility of cardiac MR thermometry at low field remains unknown. In this study, we demonstrate the feasibility of cardiac MR thermometry at 0.55T and characterized its in vivo stability (i.e., precision) using state-of-the-art techniques based on the proton resonance frequency shift method. Nine healthy volunteers were scanned using a cardiac MR thermometry protocol based on single-shot EPI imaging (3 slices in the left ventricle, 150 dynamics, TE = 41ms). The reconstruction pipeline included image registration to align all the images, multibaseline approach (look-up-table length = 30) to correct for respiration-induced phase variations, and temporal filtering to reduce noise in temperature maps. The stability of thermometry was defined as the pixel-wise standard deviation of temperature changes over time. Cardiac MR thermometry was successfully acquired in all subjects and the stability averaged across all subjects was 1.8±1.0°C. Without multi-baseline correction, the overall stability was 2.8±1.6°C. In conclusion, cardiac MR thermometry is feasible at 0.55T and further studies on MR-guided catheter ablations at low field are warranted.